Graphene- and carbon-nanotube-based transparent electrodes for semitransparent solar cells - Lee, Kyu Tae; Park, Dong Hyuk; Baac, Hyoung Won; Han, Seungyong (Materials, 2018)
A substantial amount of attention has been paid to the development of transparent electrodes based on graphene and carbon nanotubes (CNTs), owing to their exceptional characteristics, such as mechanical and chemical stability, high carrier mobility, high optical transmittance, and high conductivity. This review highlights the latest works on semitransparent solar cells (SSCs) that exploit graphene- and CNT-based electrodes. Their prominent optoelectronic properties and various fabrication methods, which rely on laminated graphene/CNT, doped graphene/CNT, a hybrid graphene/metal grid, and a solution-processed graphene mesh, with applications in SSCs are described in detail. The current difficulties and prospects for future research are also discussed.
Keywords: Fabrication method; High carrier mobility; High conductivity; Optoelectronic properties; Semi-transparent solar cells; Semitransparent; Solution-processed; CNT; Graphene; Semitransparent; Solar cells; Transparent electrodes